Design optimization for dose-finding trials: a review. Issue 4 (3rd July 2020) - Aouni, Jihane; Bacro, Jean Noel; Toulemonde, Gwladys; Colin, Pierre; Darchy, Loic; Sebastien, Bernard
ABSTRACT: Dose selection is one of the most difficult and crucial decisions to make during drug development. As a consequence, the dose-finding trial is a major milestone in the drug development plan and should be properly designed. This article will review the most recent methodologies for optimizing the design of dose-finding studies: all of them are based on the modeling of the dose–response curve, which is now the gold standard approach for analyzing dose-finding studies instead of the traditional ANOVA/multiple testing approach. We will address the optimization of both fixed and adaptive designs and briefly outline new methodologies currently under investigation, based on utility functions.